STRUCTURE AND COMPLEX THERAPY OF DORSALGIA IN CHILDREN - A. A. Smirnova; O. L. Lapochkin; M. A. Lobov; M. N. Borisova (Union of pediatricians of Russia, 2014)
The article presents results of back pain syndrome screening in a population of children according to the poll of 600 students of classes 1-11. The spread of dorsalgiae is 19%. According to the examination, nosological and clinical structure of dorsalgiae was determined in 35 children of 3-18 years of age hospitalized due to back pain. Lumbalgia was revealed in 55 (52%) patients; cervicalgia - in 31 (30%) patients; thoracalgia - in 19 (18%) patients. Juvenile osteochondrosis of lumbosacral spine is the cause of lumbosacral pain syndrome in most patients. The authors analyzed complex treatment efficacy and demonstrated that affective disorders are a prognostically significant factor of back pain onset.